2020
DOI: 10.1016/j.cmet.2020.07.016
|View full text |Cite
|
Sign up to set email alerts
|

The Immunomodulatory Metabolite Itaconate Modifies NLRP3 and Inhibits Inflammasome Activation

Abstract: The Krebs cycle-derived metabolite itaconate is highly upregulated in inflammatory macrophages and exerts immunomodulatory effects through cysteine modifications on target proteins. The NLRP3 inflammasome, which cleaves IL-1β, IL-18, and gasdermin D, must be tightly regulated to avoid excessive inflammation. Here we provide evidence that itaconate modifies NLRP3 and inhibits inflammasome activation. Itaconate and its derivative, 4-octyl itaconate (4-OI), inhibited NLRP3 inflammasome activation, but not AIM2 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
260
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(321 citation statements)
references
References 59 publications
15
260
1
Order By: Relevance
“…Previously reported results showed that ketamine and propofol can suppress LPS-induced upregulation of IL-1beta and extracellular signal-regulated kinase 1/2 (ERK1/2) phosphorylation in glia cells and brains [ 15 , 16 ]. IL-1beta is a proinflammatory cytokine and critically participates in cell activation and death of macrophage pyroptosis [ 17 , 18 ]. TNF-alpha, tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), and IFN-gamma are a potent inducer of neuron, microglia, and astroglia apoptosis after hypoxia-ischemia and inflammation [ 1 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously reported results showed that ketamine and propofol can suppress LPS-induced upregulation of IL-1beta and extracellular signal-regulated kinase 1/2 (ERK1/2) phosphorylation in glia cells and brains [ 15 , 16 ]. IL-1beta is a proinflammatory cytokine and critically participates in cell activation and death of macrophage pyroptosis [ 17 , 18 ]. TNF-alpha, tumor necrosis factor-related apoptosis-inducing ligand (TRAIL), and IFN-gamma are a potent inducer of neuron, microglia, and astroglia apoptosis after hypoxia-ischemia and inflammation [ 1 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A link between metabolism and cell death phenotypes has been investigated in many prior studies, including recent work demonstrating that the inflammasome components NLRP3 and GSDMD can be post-translationally modified by TCA cycle intermediates (Hooftman et al, 2020; Humphries et al, 2020). Moreover, metabolic dysfunction and mitochondrial damage have been considered to initiate death pathway signaling events upstream of apoptosome and inflammasome activities (Andersen and Kornbluth, 2013; Prochnicki and Latz, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…2The matrix pH changes during cellular respiration, yielding more reactive thiol groups Interestingly, itaconate-dependent activation of NRF2 was sufficient to inhibit IL-1β transcription in the context of LPS-activated macrophages. Hooftman et al expanded upon this important body of work by characterizing the effect that this immunomodulatory metabolite has on inflammasome-dependent IL-1β production and maturation [112]. More specifically, itaconate was found to alkylate Cys 548 on NLRP3, thereby inhibiting the interaction between this protein and NEK7, a partner required for inflammasome activation.…”
Section: Lipid Electrophilesmentioning
confidence: 99%
“…More specifically, itaconate was found to alkylate Cys 548 on NLRP3, thereby inhibiting the interaction between this protein and NEK7, a partner required for inflammasome activation. Additional research will be needed to evaluate if itaconate can be used as a therapeutic to treat NLRP3-driven inflammatory pathologies [111,112].…”
Section: Lipid Electrophilesmentioning
confidence: 99%